Breaking the shield of solid tumors: a combined approach for enhanced efficacy of CAR-T cells - Marat Khaliulin; Aygul Valiullina; Alexey Petukhov; Youyong Yuan; Sheila Spada; Emil Bulatov (Cancer Immunology, Immunotherapy)
Abstract The use of chimeric antigen receptor (CAR)-T cells has enhanced the range of available therapeutic modalities in the context of cancer treatment. CAR-T cells have demonstrated considerable efficacy in the targeted eradication of blood cancer cells, thereby stimulating substantial interest in the advancement of such therapeutic approaches. However, the efficacy of CAR-T cells against solid tumor cells has been limited due to the presence of various obstacles. Solid tumors exhibit antigenic diversity and an immunosuppressive microenvironment, which presents a challenge for immune cells attempting to penetrate the tumor. CAR-T cells also demonstrate decreased proliferative activity and cytotoxicity. Furthermore, concerns exist regarding tumor antigen loss and therapy-associated toxicity. Currently, scientists are working to enhance the structure of the CAR and improve the survival and efficiency of CAR-T cells in recognizing tumor antigens in solid tumors. Chemotherapy drugs are frequently employed in the treatment of malignant neoplasms and can also be used prior to cell therapy to enhance CAR-T cell engraftment. Recent studies have demonstrated that chemotherapy drugs can mitigate the suppressive impact of TME, eliminate the physical barrier by destroying the tumor stroma, and facilitate greater penetration of immune cells and CAR-T cells into the tumor. This, in turn, increases their survival, persistence, and cytotoxicity, as well as affects the metabolism of immune cells inside the tumor. However, the effectiveness of the combined approach against solid tumors depends on several factors, including the type of tumor, dosage, population of CAR-T cells, and individual characteristics of the body. This review examines the principal obstacles to the utilization of CAR-T cells against solid tumors, proposes solutions to these issues, and assesses the potential advantages of a combined approach to radiation exposure, which has the potential to enhance the sensitivity of the tumor to other agents.